Analisis Dampak Perubahan Penggunaan LahanTerhadap Prediksi Tingkat Kerawanan Erosi Di DAS Batang Pasaman 2010-2020 - Hermanto, Bambang (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Changes in land use in the Pasaman watershed are one of the factors that influence the ability of land to withstand erosion. This study aims to find out how changes in land use in the Pasaman watershed and determine the impact of changes in land use on erosion that occurs in the Pasaman watershed. This study uses a descriptive method with a quantitative approach. To determine the level of erosion hazard in the Batang Pasaman watershed, the Universal Soil Loss Equation (USLE) method was used. The level of erosion hazard in the Batang Pasaman watershed was different in 2010, 2015 and 2020. Where in 2010 and 2015 the type of very low erosion hazard was still quite extensive, namely 74% and 79% respectively of the total area of ​​the Batang Pasaman watershed, for the type very severe erosion hazard has the same area which is equal to 1% of the total area. Whereas in 2020 the type of very low erosion hazard will decrease to 51% and the type of very severe erosion hazard will increase to 2%.